PENGARUH CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN PENGENDALIAN INTERNAL PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Stefany Stefany; Henryanto Wijaya (Jurnal Bina Akuntansi, 2018)
The purpose of this research was to obtain and analyze empirical evidence about the effect of corporate governance (board size, independent commissioner, managerial ownership, institutional ownership, audit committee size, and audit committee education) on internal control disclosure. Research carried out on 30 banking companies listed on the Indonesia stock exchange (BEI) in the period 2013 – 2015. The statistical method used to test the hypothesis of the research is a multiple linear regression model. Therefore, before testing the hypothesis, a number of classic assumption test need to be conducted first. With a 95% confidence level, research shows that board size, managerial ownership, and audit committee size have a significant influence on internal control disclosure, while independent commissioner, institutional ownership, and audit committee size not have a significant effect on internal control disclosure. Should further research can increase the population of companies other than the banking companies and can add independent variables.